PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS X PADA MATERI SPtLDV - Ahmad Miftahul Farohi; Ihsanudin Ihsanudin (LPPM Universitas Bina Bangsa, 2023)
This research aims to determine whether the application of the cooperative learning model in the process of learning mathematics in SPtLDV material has an influence or not on student learning outcomes. The subjects in this study were students of class X IPA 1 at SMAS MALNU Menes Center, totaling 20 students, consisting of 4 male students and 16 female students. The type of research used is a pre-experimental design with the type one-group pretest-posttest design. The data collection technique used is through pretest and posttest. The data analysis technique used is the normality test and paired t-test hypothesis with the help of SPSS software. From the results of the research conducted, it can be seen that the p-value (sig. (2-tailed)) in the paired t-test <0.05. This shows that there is a significant difference between before and after applying the cooperative learning model in the mathematics learning process. In addition, this can also be seen from the average score before (pretest) and after (posttest) applying the cooperative learning model, namely the average score in the pretest is 59,5, while the average score in the posttest is 72,5. So it can be concluded that the application of the cooperative learning model in the mathematics learning process SPtLDV material influences the learning outcomes of class X IPA 1 students at SMAS MALNU Pusat Menes